A Survey on Fish Population Availability in Different Season in Northern India - Shikha Gomra; Sunaina Chandel; Atif Zargar; Arup Giri (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
Among all the animal protein sources, fish is the best dietary animal protein source due to the presence of less saturated fat and readily available in the market. A survey on fish availability in the fish market has pasteurized the seasonal availability of the different species of fishes. The Present study conducted on the availability of different fish species during the summer, spring, and winter months at the Gummat fish market, Jammu Division; Bilaspur fish market, Himachal Pradesh; Amritsar fish market, Punjab. The survey result showed that in all the fish markets, the price of the fish was higher in the winter season than in the summer season. Mainly Labeo rohita, Tor mosal, Catla catla, Wallago attu, Bramidae, Anabas testudineus, Carassiusauratus, Catla catla, Ctenophoryngodon idella, Labeo rohita, Lethrinus bohar, Nandus nandus, Pampus chinensis, Pangasius buchanani, Platycephalus fuscus, Rita rita, Solea solea, Sperata seenghala, Telopia nilotica, Tenualosa ilish were found in these markets throughout the season. In the case of body weight and body length of different fish species, it has been found that bodyweight greatly varied in the summer and winter months. Lower availability and insufficient body weight of different fish species in the winter month affects the income of fish sellers of this market. From this study, it might be concluded that variable price, the low body weight of fish species may affect the income of fish sellers in this market. A special lookout should have to be taken by the state fisheries department so that the continuous fish supply may take place in this market.